Framework to assess the impact of the AfCFTA Protocol on Digital Trade - Alberto Lemma (ODI, 2024)
The African Continental Free Trade Area (AfCFTA) Protocol on Digital Trade represents a significant step forward for Africa's economic integration and digital transformation. This report assesses the Protocol's potential to reshape the continent's economic landscape by fostering a unified digital market, promoting digital inclusion, and overcoming existing trade barriers. The Protocol is expected to boost intra-African trade, create millions of jobs, and contribute billions to the continent's GDP. It will enhance connectivity, spur innovation, and attract investment, driving economic growth and development across Africa. The report also explores the Protocol's impact on cybersecurity, data protection, and the ethical use of emerging technologies. It underscores the need for international cooperation and support from governments to enhance digital infrastructure and foster an environment conducive to digital innovation. The AfCFTA Protocol on Digital Trade is not just a trade agreement; it is a blueprint for Africa's digital future. It offers a vision of an interconnected, innovative, and inclusive continent that harnesses the power of digital technology for sustainable development. By addressing existing challenges and ensuring equitable access to digital opportunities, the Protocol can unlock Africa's digital potential, foster economic integration, and drive inclusive growth for all Africans.
Keywords: 330; Digital; Economic transformation; Economic growth; Africa; Trade & investment